METHODOLOGICAL RECOMMENDATIONS FOR USING THE HISOBLY PLATFORM - Soliyeva Gavharoy Yodgorjon qizi (Web of Journals Publishing, 2026)
This thesis examines the appearance of the software and methodological complex for "Computational Methods" taught in higher education institutions, experimental research work, and educational content of the platform. Also, the methodological guide "Methodological recommendations for working on the Hisobly platform" on the use of the software and methodological complex was reviewed.
Keywords: Computational methods, software and methodological complex, experimental research, educational content, Hisobly platform.